THE RESOLUTION OF SOCIAL CONFLICT IN THE NATIONAL CONSTITUTION AND ISLAMIC PERSPECTIVES: Integrating Formal and Non-Formal Approaches - Hanafi, Yusuf; Thoriquttyas, Titis (IAIN Ponorogo, 2018)
Abstract: Social conflict resolution is often viewed as a complex matter. Thus, a non-formal approach is needed to complement the formal approach of Law No.7 of 2012 that was legalized by The House of Representatives of the Republic of Indonesia several years ago. It is not uncommon for non-formal conflict resolution to be more effective since it has a broader acceptance in society. A non-formal approach does not mean to undermine the existing laws; it can even complement it and become an alternative solution when the formal approach does not work. This study aims to describe the model of social conflict resolution based on Law No.7 of 2012 and the Quran as a comprehensive combination in resolving social conflict through a formal and non-formal approach. This study discusses that the Quran has a unique formula in resolving social conflicts by emphasizing the principal of kindness to prevent conflicts and implementing justice as a resolution to conflicts.Ø§Ù„Ù…Ù„Ø®Øµ: Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ ÙƒØ«ÙŠØ±Ø§ Ù…Ø§ ÙŠÙƒÙˆÙ† Ø£Ù…Ø±Ø§ ØµÙŽØ¹Ù’Ø¨Ø§Ù‹ ØªØ¯ÙˆÙ’Ø±Ù ØÙˆÙ„Ù‡ Ø£Ø¨Ø¹Ø§Ø¯ÙŒ Ù…Ø¹Ù‚Ù‘ÙŽØ¯ÙŽØ©ÙŒ, ÙˆÙ‡Ù†Ø§Ùƒ ØØ§Ø¬Ù‘Ø©ÙŒ Ù…Ø§Ø³Ù‘Ø©ÙŒ Ù„Ù…Ø¹Ø§Ù„Ø¬ØªÙÙ‡ Ù…Ù† Ø§Ù„Ù†Ù‘Ù‡Ø¬ ØºÙŠØ± Ø§Ù„Ø±Ø³Ù…ÙŠÙ‘ Ø¨Ø¬Ø§Ù†Ø¨ Ø§Ù„Ù†Ù‡Ø¬ Ø§Ù„Ø±Ø³Ù…ÙŠÙ‘ Ø§Ù„Ù‘Ø°ÙŠ Ù‚Ø±Ù‘ÙŽØ±ÙŽÙ‡ Ù…Ø¬Ù„Ø³Ù Ø§Ù„Ù†Ù‘ÙˆØ§Ø¨ Ø§Ù„Ø´Ø¹Ø¨ÙŠ Ø¨ÙˆØ§Ø³Ø·Ø© Ø§Ù„Ù‚Ø§Ù†ÙˆÙ† Ø±Ù‚Ù… 7 Ø³Ù†Ø© 2012 Ø¹Ø¯Ø© Ø³Ù†ÙˆØ§Øª Ù…Ø§Ø¶ÙŠØ©, Ø¥Ø°Ù’ Ù‚Ø¯ ÙŠÙƒÙˆÙ† Ø§Ù„Ù†Ù‡Ø¬ ØºÙŠØ± Ø§Ù„Ø±Ø³Ù…ÙŠÙ‘ Ø£ÙƒØ«ÙŽØ±ÙŽ ÙØ¹Ø§Ù„ÙŠØ©Ù‹ ÙˆÙ‚Ø¨ÙˆÙ„Ù‹Ø§ Ù„Ø¯Ù‰ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ ÙÙŠ Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ. ÙˆÙ‡Ø°Ø§ Ø§Ù„Ù†ÙˆØ¹ Ù…Ù† Ø§Ù„Ù†Ù‡Ø¬ Ù„Ø§ ÙŠØ¹Ù†ÙŠ Ø¥Ù„ØºØ§Ø¡ Ø§Ù„Ù‚Ø§Ù†ÙˆÙ† Ø§Ù„ÙˆØ·Ù†ÙŠ Ø§Ù„Ø±Ø³Ù…ÙŠ, Ø¨Ù„ ÙŠØ³ÙØ¯Ù‘ÙÙ‡ ÙˆÙŠÙƒÙ…Ù‘ÙÙ„ÙÙ‡Ù â€”Ø®ØµÙˆØµØ§ Ø¥Ø°Ø§ ÙƒØ§Ù† Ù‡Ù†Ø§Ùƒ Ø¹ÙˆØ§Ø¹ÙÙ‚Ù ØªØ¹ÙˆÙ‚Ù Ø¯ÙˆÙ† Ù†Ø¬Ø§Ø. ØªØ³ØªÙ‡Ù’Ø¯ÙÙÙ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„ÙŽØ©Ù Ø¥Ù„Ù‰ ÙˆØµÙ Ø§Ù„Ù†Ù…Ø§Ø°Ø¬ ÙÙŠ Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ Ù…Ù† ÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø§Ù„Ù‚Ø§Ù†ÙˆÙ† Ø±Ù‚Ù… 7 Ø³Ù†Ø© 2012 ÙˆÙˆØ¬Ù‡Ø© Ù†Ø¸Ø± Ø§Ù„Ø¥Ø³Ù„Ø§Ù…, Ø±Ø¬Ø§Ø¡Ù‹ Ø§Ù„ØØµÙˆÙ„ Ø¹Ù„Ù‰ Ø§Ù„Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„Ù…Ø«Ø§Ù„ÙŠ Ø§Ù„Ù…ØªÙƒØ§Ù…Ù„ Ù„Ù‡Ø°Ù‡ Ø§Ù„Ù‚Ø¶ÙŠØ©. ØªØµÙ Ù‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© Ø£Ù† Ù„Ù„Ù‚Ø±Ø¢Ù† ØµÙŠØºØ© Ø®Ø§ØµØ© Ù…ØªÙ…ÙŠØ²Ø© ÙÙŠ Ù…Ø¹Ø§Ù„Ø¬Ø© Ø§Ù„Ù†Ù€Ø²Ø§Ø¹ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ, ÙˆÙ‡Ùˆ ØªØ£ÙŠÙŠØ¯